Higher mortality risk among injured individuals in a population-based matched cohort study - Rebecca J. Mitchell; Cate M. Cameron; Rod McClure (BMC, 2017)
Abstract Background Improved understanding of long-term mortality attributable to injury is needed to accurately inform injury burden studies. This study aims to quantify and describe mortality attributable to injury 12 months after an injury-related hospitalisation in Australia. Method A population-based matched cohort study using linked hospital and mortality data from three Australian states during 2008-2010 was conducted. The injured cohort included individuals ≥18 years who had an injury-related hospital admission in 2009. A comparison cohort of non-injured people was obtain by randomly selecting from the electoral roll. This comparison group was matched 1:1 on age, gender and postcode of residence. Pre-index injury health service use and 12-month mortality were examined. Adjusted mortality rate ratios (MRR) and attributable risk were calculated. Cox proportional hazard regression was used to examine the effect of risk factors on survival. Results Injured individuals were almost 3 times more likely to die within 12 months following an injury (MRR 2.90; 95% CI: 2.76-3.04). Individuals with a traumatic brain injury (MRR 7.58; 95% CI: 5.92-9.70) or injury to internal organs (MRR 7.38; 95% CI: 5.90-9.22) were 7 times more likely to die than the non-injured group. Injury was likely to be a contributory factor in 92% of mortality within 30 days and 66% of mortality at 12 months following the index injury hospital admission. Adjusted mortality rate ratios varied by type of cause-specific death, with MRR highest for injury-related deaths. Conclusions There are likely chronic consequences of sustaining a traumatic injury. Longer follow-up post-discharge is needed to consider deaths likely to be attributable to the injury. Better enumeration of long-term injury-related mortality will have the potential to improve estimates of injury burden.